Abundance of antibiotic resistance genes and bacterial community composition in wild freshwater fish species - Marti, Elisabet; Huerta, Belinda; Rodríguez-Mozaz, Sara; Barceló, Damià; Marcé, Rafael; Balcázar, Jose Luis (Chemosphere, 2018)
This study was aimed to determine the abundance of four antibiotic resistance genes (blaTEM, ermB, qnrS and sulI), as well as bacterial community composition associated with the intestinal mucus of wild freshwater fish species collected from the Foix and La Llosa del Cavall reservoirs, which represent ecosystems with high and low anthropogenic disturbance, respectively. Water and sediments from these reservoirs were also collected and analyzed to determine the pollution level by antibiotics. The blaTEM gene was only detected in brown trout and Ebro barbel, which were collected from La Llosa del Cavall reservoir. In contrast, the sulI and qnrS genes were only detected in common carp, which were collected from the Foix reservoir. Although the ermB gene was also detected in common carp, the values were below the limit of quantification. Likewise, water and sediment samples from the Foix reservoir had higher concentrations and more classes of antibiotics than those from La Llosa del Cavall. Pyrosequencing analysis of 16S rRNA genes revealed significant differences in bacterial communities associated with the intestinal mucus of fish species. Therefore, these findings suggest that anthropogenic activities are not only increasing the pollution of aquatic environments, but also contributing to the emergence and spread of antibiotic resistance in organisms that inhabit such environments.
Keywords: Antibiotic resistance genes; Aquatic environments; Bacterial community composition; Wild fishes; dept.che

Effects of subinhibitory ciprofloxacin concentrations on the abundance of qnrS and composition of bacterial communities from water supply reservoirs - Marti, Elisabet; Huerta, Belinda; Rodríguez-Mozaz, Sara; Barceló, Damià; Balcázar, Jose Luis; Marcé, Rafael (Chemosphere, 2016)
We used a short-term microcosm approach to investigate the influence of two different subinhibitory concentrations of ciprofloxacin (0.01 and 0.1 μg/ml) on both the abundance of a plasmid-mediated quinolone resistance determinant (qnrS) and the structure and composition of bacterial communities from impaired and pristine water supply reservoirs. The results showed that the abundance of the qnrS gene increases in water samples exposed to both subinhibitory concentrations of ciprofloxacin, especially in water samples from La Llosa del Cavall, which represents the pristine system. Subinhibitory ciprofloxacin concentrations also induced changes in bacterial community composition as indicated by the relative abundances of each operational taxonomic unit (OTU) across treatments. Therefore, our findings may be of significant importance because subinhibitory ciprofloxacin concentrations may promote antibiotic resistance and affect bacterial community composition in environmental settings.
Keywords: Antibiotic resistance genes; Aquatic systems; Bacterial community; Quinolones; Water supply reservoirs; dept.che